Magnetorotational instability in neutron star mergers: impact of neutrinos. Issue 2 (13th July 2017) - Guilet, Jérôme; Bauswein, Andreas; Just, Oliver; Janka, Hans-Thomas
Abstract: The merger of two neutron stars may give birth to a long-lived hypermassive neutron star. If it harbours a strong magnetic field of magnetar strength, its spin-down could explain several features of short gamma-ray burst afterglows. The magnetorotational instability (MRI) has been proposed as a mechanism to amplify the magnetic field to the required strength. Previous studies have, however, neglected neutrinos that may have an important impact on the MRI by inducing a viscosity and drag. We investigate the impact of these neutrinos effects on the linear growth of the MRI by applying a local stability analysis to snapshots of a neutron star merger simulation. We find that neutrinos have a significant impact inside the hypermassive neutron star, but have at most a marginal effect in the torus surrounding it. Inside the hypermassive neutron star, the MRI grows in different regimes depending on the radius and on the initial magnetic-field strength. For magnetic fields weaker than 10 13 –10 14  G, the growth rate of the MRI is significantly reduced due to the presence of neutrinos. We conclude that neutrinos should be taken into account when studying the growth of the MRI from realistic initial magnetic fields. Current numerical simulations, which neglect neutrino viscosity, are only consistent, i.e. in the adopted ideal regime, if they start from artificially strong initial magnetic fields above ∼10 14  G. One should be careful when extrapolating these results to lower initial magnetic fields, where the MRI growth is strongly affected by neutrino viscosity or drag.